DONOR SITE MORBIDITY OF FIBULAR FLAP - Ghazanfar Ali; Abdul Majid; Danish Almas; Shahid Hameed; Rizwan Aslam; Zubair Ahmad Khan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To present the early and late outcomes related to donor site morbidity of Free Fibular Flap.